Akt and estrogen receptor expression in nasal polyps - Selen Bahçeci; Fatma Şimşek; Erdem Eren; Ibrahim Aladaǧ (Wolters Kluwer Medknow Publications, 2019)
Background: Nasal polyps (NP) is a common chronic inflammatory disease of the mucous membranes in the nose and paranasal sinuses. The underlying mechanisms of pathologic conditions to NP formation remains unclear. The aim of this study is to evaluate the expression of Akt and estrogen receptor (ER) in nasal polyps. Material and Methods: We respectively obtained 20 nasal polyp tissue and 15 concha from patients undergoing endoscopic polyp biopsy and turbinate resection. All samples were fixed in 10% formalin for 24 h and embedding in paraffin was using routine protocol for histological prepation. Sections 5 μm thick were cut and stained H&E. Tissue samples were stained with anti-ER and anti-Akt primary antibody, ER and Akt were evaluated immunohistochemically. There is a relationship between the estrogen receptor and PI3K/Akt signaling pathway in malignansy. In this study, it showed the effect of estrogen on the activation of Akt signaling pathway in nasal polyps. Mann- Whitney-U test was applied to evaluate the statistical differences between nasal polyp and control group, (P < 0.05) was accepted as significant. Results: In H&E stained sections we observed a lot of inflamatory cells and eosinophils in the mucosa, submucosal connective tissue and around the glandular epithelium in nasal polyps. The mucosa and submucosal connective tissue was seen normally in control group in H&E stained. We determined that ER and Akt were intensely expressed in nasal polyps. Expression is localized especially in epithelial and glandular epithelium cells and submucosal connective tissue. In contrast, expression of ER and Akt were mildly expressed in turbinate resection samples. Conclusion: The expression of ER and Akt might be important factors in nasal polyp pathogenesis and may shed new light on clinical approaches in nasal polyp treatment.